Notebook from the lectures of Herman Mark, 1929 - Bredig, Georg (1929)
Notebook belonging to Georg Bredig (1868-1944). Contents have notes from lectures by Herman Francis Mark (1895-1992). Mark was an Austrian chemist known for his contributions to polymer science, X-ray diffraction, and his work at IG Farben. In 1938 Mark began preparing to leave Austria but Hitler invaded Austria before he could leave the country. Mark was sent to a Gestapo prison. After his release, he was able to immigrate to America by first entering Canada. He continued his research in polymers in Brooklyn, New York.
Keywords: Bredig, Georg, 1868-1944; Notebooks; Catalysts; Mark, H. F. (Herman Francis), 1895-1992; Chemists